Early Relay Intercropping of Short-Season Cotton Increases Lint Yield and Earliness by Improving the Yield Components and Boll Distribution under Wheat-Cotton Double Cropping - Guoping Wang; Lu Feng; Liantao Liu; Yongjiang Zhang; Anchang Li; Zhanbiao Wang; Yingchun Han; Yabing Li; Cundong Li; Hezhong Dong (Agriculture, 2021)
Wheat-cotton double cropping has improved crop productivity and economic benefits per unit land area in many countries, including China. However, relay intercropping of full-season cotton and wheat, the most commonly adopted mode, is labor-intensive and unconducive to mechanization. The direct sowing of short-season cotton after wheat (CAW) has been successful, but cotton yields and economic benefits are greatly reduced. Whether the relay intercropping of short-season cotton before the wheat harvest increases cotton yields remains unclear, as does the earliness and fiber quality relative to those for CAW. Therefore, we directly planted short-season cotton after wheat harvest on 15 June (CAW) as the control and interplanted short-season cotton in wheat on 15 May (S1), 25 May (S2) and 5 June (S3), which were 30, 20 and 10 days prior to wheat harvest, respectively, from 2016 to 2018. The crop growth, yield, yield components, boll distribution, and earliness of the cotton were evaluated. The yields and earliness of short-season cotton under relay intercropping were 26.7–30.6% and 20.4–42.9% higher than those under CAW, respectively. Compared with CAW, relay intercropping treatments increased the boll density, boll weight and lint percentage by 5.6–13.1%, 12.5–24.5% and 5.8–12.7%, respectively. The dry matter accumulation and harvest index under the relay intercropping treatments were also greater than those under CAW, which might be attributed to the greater partitioning of dry matter to the seed cotton than to the boll shells. Among the relay intercropping treatments (S1, S2 and S3), the lint yield did not differ, but S1 and S2 were considerably better than S3 based on earliness and fiber quality. The analysis of the within-plant spatial boll distribution showed that more bolls were formed on the lower to middle fruiting branches and at the first fruiting sites for S1 and S2 than for S3 and CAW. Therefore, the increased earliness and fiber quality induced through early relay intercropping (S1 and S2) could be attributed to an improved spatial boll distribution compared to late relay intercropping (S3) or CAW. Conclusively, compared to late relay intercropping and CAW, early relay intercropping considerably increased the lint yield, fiber quality, and earliness by improving the yield components, boll distribution, and dry matter accumulation and partitioning. The relay intercropping of short-season cotton 20 to 30 days before wheat harvest represents a promising alternative to CAW in wheat-cotton double-cropping systems in the Yellow River Basin of China and other regions with similar conditions.